2021
DOI: 10.20463/pan.2021.0021
|View full text |Cite
|
Sign up to set email alerts
|

Improving hydration in elite male footballers during a national team training camp – an observational case study

Abstract: [Purpose] The purpose of this study was to (i) assess hydration levels in elite male football players during a national team training camp before and during qualifying matches, (ii) evaluate the effect of coaching strategies for hydration based on feedback from hydration monitoring, and (iii) assess possible relationships between hydration status and training load or wellness markers.[Methods] Thirty-one male players (age 27±4 yrs; height 185±6 cm; weight 82.9±6.7 kg; body fat 10.4±2.3%) representing a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Soccer is practiced all over the world, and male soccer players are among the most studied groups of athletes in sports sciences [ 1 , 2 , 3 ]. Soccer players at a high level require highly developed physical capacities, psychological factors, and perceptual, cognitive, and motor skills such as running, jumping, heading, kicking, passing, dribbling, and balance [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soccer is practiced all over the world, and male soccer players are among the most studied groups of athletes in sports sciences [ 1 , 2 , 3 ]. Soccer players at a high level require highly developed physical capacities, psychological factors, and perceptual, cognitive, and motor skills such as running, jumping, heading, kicking, passing, dribbling, and balance [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The total sweat rate was 2.04 ± 0.57 L during first 90 min of soccer match play in the study by Mohr et al (2023), and the lead author's research group previously reported that many professional soccer players are typically hypo-hydrated [36]. The monitoring and coaching of hydration status and strategies, respectively, can improve hydration among professional soccer players [36]. Although the intake of carbohydrate-electrolyte gels improved blood glucose levels and soccer dribbling performance during an extra-time period of a simulated match, it did not attenuate reductions in hydration status or CMJ height [37].…”
Section: Discussionmentioning
confidence: 88%
“…Although alterations in muscle glycogen stores post-match may be considered more of a metabolic than neuromuscular response, a recent study showed that through a principal component analysis, a force plate assessment of the CMJ can distinguish metabolic fatigue from NMF [35]; however, more research involving this approach is required. The total sweat rate was 2.04 ± 0.57 L during first 90 min of soccer match play in the study by Mohr et al (2023), and the lead author's research group previously reported that many professional soccer players are typically hypo-hydrated [36]. The monitoring and coaching of hydration status and strategies, respectively, can improve hydration among professional soccer players [36].…”
Section: Discussionmentioning
confidence: 89%
“…The total sweat rate was 2.04 ± 0.57 L during normal time, which is within the range usually observed in other studies at moderately high temperature ( 30 ), but rose to nearly 3.5 L during extra time, resulting in a 26% higher sweat rate in extra time compared with normal time. Despite the fact that no difference was observed in hematocrit levels between the 90- and 120-min time points, dehydration may become a component contributing to deteriorated performance in the extra-time period, especially because a high number of elite soccer players are hypohydrated in normal conditions ( 43 ).…”
Section: Discussionmentioning
confidence: 99%